Tingkat Keberhasilan Telur Tetas Ayam Kampung Unggul Balitbangtan (KUB) Terhadap Masa Simpan Yang Berbeda: The Success Rate of Balitbangtan (KUB) Superior Native Chicken Hatching Eggs (KUB) Against Different Shelf Periods - Amelia, Rizki; Mudawaroch, Roisu Eny; Nurfaizin, Nurfaizin (Universitas Muhammadiyah Purworejo, 2025)
KUB chickens have the potential to be developed. KUB chicken breeders need to be reproduced by artificial hatching. This study aims to determine the effect of egg storage period on egg weight, fertility, hatchability and DOC weight in superior free-range chickens of IAARD (KUB). The research was carried out from April to May 2025 and egg hatching lasted for one month in the cage of the Agricultural Assembly and Modernization Agency (BRMP). This study used a Complete Random Design (RAL) with 6 shelf life treatments and 4 replicates, each consisting of 4 eggs. The parameters measured were egg weight, fertility, hatchability, and DOC weight of superior free-range chickens of IAARD (KUB). The tools and materials used in this study were 96 eggs of IAARD superior free-range chicken eggs (KUB) and 2 units of automatic hatching machines. The data obtained were analyzed using the Analysis of Variance (ANOVA) and the follow-up test of Duncan's Multiple Range Test (DMRT). The results showed that the shelf life of Kampung Unggul IAARD (KUB) chicken eggs had a real effect (P<0.05) on egg weight on the 1st day of storage, but had no real effect (P>0.05) on days 7, 14, and 18. In addition, the fertility of KUB chickens had a real effect (P<0.05) on the weight of hatching eggs, but the shelf life had no real effect (P>0.05) on hatchability or the weight of the DOC produced. The conclusion of this study shows that different storage periods have a real effect on the weight of eggs on day 1 and the fertility of the open-air chickens of IAARD (KUB). Meanwhile, hatchability and weight of DOC showed no noticeable effect due to different shelf life.